2018
DOI: 10.1177/0954407018759739
|View full text |Cite
|
Sign up to set email alerts
|

Effects of split and single injection strategies on particle number emission and combustion of a GDI engine

Abstract: Influence of fuel injection parameters of the single and split injection strategies on combustion, performance and particle number emission had been investigated on a gasoline direct injection engine with stoichiometric mixture combustion under medium and low engine operating conditions. The test results showed that the optimal injection timing for single injection strategy was about 290–280 °CA BTDC, and an earlier or a later injection timing could lead to a deterioration of particle number emission. For spli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 32 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…Moreover, Zhuang et al 27 found that a significant oil-rich zone would appear in the center of the cylinder at delayed injection timing, which made nitrogen oxides (NO x ) emissions increase. Xie et al 28 found experimentally that the presence of optimal injection timing resulted in the best emissions performance. Further, Firat 29 indicated that compared to single-injection strategy, multistage injection strategies reduce the direct injection spark ignition (DISI) engine emissions such as NO x , carbon monoxide (CO), and unburned hydrocarbon (UHC).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Zhuang et al 27 found that a significant oil-rich zone would appear in the center of the cylinder at delayed injection timing, which made nitrogen oxides (NO x ) emissions increase. Xie et al 28 found experimentally that the presence of optimal injection timing resulted in the best emissions performance. Further, Firat 29 indicated that compared to single-injection strategy, multistage injection strategies reduce the direct injection spark ignition (DISI) engine emissions such as NO x , carbon monoxide (CO), and unburned hydrocarbon (UHC).…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Particulate emissions are highly sensitive to the start of combustion timing as well as the properties of the engine, its speed, and the spark advance. 8,9 For example, Xie et al 10 showed that delaying the spark advance from 25 CAD to 5 CAD can reduce particulate emissions from GDI engines by 50%. In a typical GDI engine drive cycle, particulate emissions peak during cold starts and transients, when there is an abrupt change in engine load or both load and speed together.…”
Section: Introductionmentioning
confidence: 99%